On propagation characteristics of ultrasonic guided waves in helical strands - Zhang, Hongyan (2023)
Steel strands have been widely used in industrial fields as a reliable load-bearing component. Under the influence of environmental erosion and fatigue stress, different types of damage, such as corrosion and fracture, will occur in the in-service steel strands, which will cause unpredictable loss of personnel and property. Ultrasonic nondestructive testing technology has become an ideal testing method for long-distance metal structures in recent years due to the advantages of long detection distance and high efficiency. The detection effect of ultrasonic nondestructive testing technology largely depends on the propagation characteristics of the selected guided wave modes. However, due to the influence of the helical structure of the steel strands and the contact between the wires, the propagation characteristics of the guided waves in the steel strands are very complicated. In this paper, a method for analyzing the dispersion characteristics of steel strands based on the Floquet boundary conditions (Floquet BCs) is proposed. The essence of this method is the mutual transformation principle of wave solution and vibration solution. To adapt to the helical structure of steel strands, this paper proposes a helical coordinate system and twisted coordinate system and deduces the corresponding wavenumber conversion formula. The results of Floquet BCs are consistent with the semi-analytical finite element method and sweep frequency finite element modeling method, which proves the correctness of the Floquet BC method from both theoretical and experimental perspectives. This paper provides a new idea for analyzing the dispersion characteristics of complex waveguides such as steel strands.